Preparation of Roselle (Hibiscus sabdariffa L.) Powder by Different Drying Methods - Angadi, Halesh; Karadiguddi, Manjula; Gorabal, Kirankumar; Patil, R. T.; Hiremath, J. S. (International Journal of Economic Plants, 2026)
The experiment was conducted during November, 2024 to 2025 at the Department of Postharvest Management, Kittur Rani Channamma College of Horticulture, University of Horticultural Sciences, Bagalkot, Arabhavi, Belagavi District, Karnataka, to study the influence of pre-treatments and different drying methods on the quality of roselle powder. The roselle powder was prepared by following a Factorial Completely Randomized Design (FCRD) consisting of twelve treatments with three replications. The experiment included two factors: pre-treatments (without blanching, steam blanching for one minute and steam blanching for two minutes) and drying methods (sun drying, shade drying, solar drying and cabinet drying at 60°C). The samples were analysed to determine the effects of these treatments on the physical parameter’s recovery (%), moisture content (%) and water activity and chemical parameters including anthocyanin (mg 100 g-1), total phenols (mg GAE 100 g-1) and antioxidant activity (%) of the end product. Among the various treatments, the roselle powder that was prepared with steam blanching for one minute followed by cabinet drying at 60°C was found to be superior with respect to both physical and chemical properties. It showed desirable physical characteristics with a recovery of 10.50%, a moisture content of 10.14% and a water activity of 0.29. The chemical composition recorded higher values with anthocyanin content of 243.15 mg 100 g-1, total phenols of 321.50 mg GAE 100 g-1, and antioxidant activity of 71.39%, indicating better colour stability and improved nutritional quality.